Development of national network and corporate networks (in the case of Tas-IX network) - Dadamukhamedov Alimjon Irgashevich (International Journal of Human Computing Studies, 2019)
This article is devoted to the development of the national data network of Uznet and Tas-IX, the history and development of Tas-IX, to improve the efficiency of using international communication channels, by excluding the transfer of local traffic over them. Strengthening the economic state of small and medium-sized businesses in the telecommunications sector by reducing their production costs for traffic transmission. The aim of the work is to directly contribute to the development of information and communication technologies in the telecommunications market of Uzbekistan. Promotes the development of the Uzbek Internet segment as a factor in the overall development of the society and raising the level of education in it, including by accessing the Internet resources of scientific, educational, state and business institutions